2023
DOI: 10.3390/genes14030729
|View full text |Cite
|
Sign up to set email alerts
|

Internal Transcribed Spacer and 16S Amplicon Sequencing Identifies Microbial Species Associated with Asbestos in New Zealand

Abstract: Inhalation of asbestos fibres can cause lung inflammation and the later development of asbestosis, lung cancer, and mesothelioma, and the use of asbestos is banned in many countries. In most countries, large amounts of asbestos exists within building stock, buried in landfills, and in contaminated soil. Mechanical, thermal, and chemical treatment options do exist, but these are expensive, and they are not effective for contaminated soil, where only small numbers of asbestos fibres may be present in a large vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Asbestos-contaminated soil samples also showed indications of fibril amorphization. Unfortunately, no DNA sequence data were available for these particular samples, but other asbestos-contaminated soil samples from the same areas were sequenced by Doyle et al [38], who identified a range of fungal and bacterial species as being present, including Cladosporium cladosporoides, Epicoccum nigrum, Fusarium oxysporum and Yarrowia lipolytica, all of which have been reported in the literature as being able to produce siderophores in vitro [16,36,39,40]. Previous research by Martino et al [19] found that several soil fungi were able to remove iron from crocidolite fibres in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Asbestos-contaminated soil samples also showed indications of fibril amorphization. Unfortunately, no DNA sequence data were available for these particular samples, but other asbestos-contaminated soil samples from the same areas were sequenced by Doyle et al [38], who identified a range of fungal and bacterial species as being present, including Cladosporium cladosporoides, Epicoccum nigrum, Fusarium oxysporum and Yarrowia lipolytica, all of which have been reported in the literature as being able to produce siderophores in vitro [16,36,39,40]. Previous research by Martino et al [19] found that several soil fungi were able to remove iron from crocidolite fibres in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that asbestos fibres can be partially degraded, and the surface reactivity reduced, by the activity of some fungi, bacteria and lichens, and that this is due to removal of metal ions, including iron, by siderophores and similar iron-chelating compounds (Bhattacharya et al 2015;Daghino et al 2006;Daghino et al 2008;Daghino et al 2010;Favero-Longo et al 2005;Favero-Longo et al 2007;Mohanty et al 2018). Several studies have shown that a range of bacteria, cyanobacteria, filamentous fungi, yeast fungi and lichenised fungi are able to colonise asbestos and related mineral deposits (Bhattacharya et al 2016;Daghino et al 2008, Daghino et al 2009Doyle et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For microbial bioremediation to be successful, it is necessary to assemble a library of potential siderophore-producing bacteria or fungi that are well suited to the environmental conditions of the local area (Doyle et al 2023). Production of siderophores in candidate isolates can be detected by culturing them on chrome azurol S (CAS)-agar plates.…”
Section: Introductionmentioning
confidence: 99%